1992
DOI: 10.1002/ijc.2910500519
|View full text |Cite
|
Sign up to set email alerts
|

Androgen regulation of prolactin‐receptor gene expression in MCF‐7 and MDA‐MB‐453 human breast cancer cells

Abstract: Lactogenic hormones which bind to the PRLR are likely to be growth-stimulatory in human breast-cancer cells. Oestrogen and progesterone control cellular expression of the PRLR; however, elevated androgen levels in some breast-cancer patients raised the possibility that androgens may also influence breast-cancer sensitivity to lactogenic hormones. This study investigated whether androgens could affect expression of the PRLR in the MCF-7 breast-cancer cell line. PRLR binding activity was increased approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Progesterone inhibits PRL-mediated expression of milk protein in mammary epithelial cells by an interaction of progesterone receptor with the signal transducer and transcription activator STAT5 (Gass et al 1998). 17 -Estradiol has been reported to increase milk protein expression by increasing PRL receptors (Mizoguchi et al 1997, Ormandy et al 1992a.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone inhibits PRL-mediated expression of milk protein in mammary epithelial cells by an interaction of progesterone receptor with the signal transducer and transcription activator STAT5 (Gass et al 1998). 17 -Estradiol has been reported to increase milk protein expression by increasing PRL receptors (Mizoguchi et al 1997, Ormandy et al 1992a.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that progestin treatment of T-47D and MCF-7 cells increased the level of PRLR binding activity (Murphy et al, 1986) and that this effect was progesterone receptor mediated (Ormandy et al, 1992). In the current work, the molecular basis for these observations was investigated.…”
Section: Discussionmentioning
confidence: 93%
“…This consideration gains support from the fact that prolactin exerts a considerable influence on chemically induced mammary carcinogenesis [107][108][109]. Moreover, several in vitro studies also show that androgens induce expression of the prolactin receptor [110] as well as stimulate expression and secretion of prolactin in uterine stromal cells [111]. Thus, the lactational alterations in neonatally androgenized female rats may be due to increased function of prolactin-prolactin receptor signaling.…”
Section: Uses Of Androgens In Womenmentioning
confidence: 99%
“…Since progesterone has a complicated influence on the mammary epithelia, including both growth stimulation and inhibition [287], it remains possible that the reported dual functions of androgens may actually be a reflection of their progestational effects. In addition, androgens have been shown to stimulate expression and secretion of prolactin from uterine stromal cells [111] and to induce expression of the prolactin receptor in human breast cancer cells [110]. Neonatal androgenization also increases the secretion of prolactin from pituitary during adulthood [94;106].…”
Section: Uses Of Androgens In Womenmentioning
confidence: 99%